A Selective Encryption Algorithm Based on AES for Medical Information - Ju-Young Oh; Dong-Il Yang; Ki-Hwan Chon (Healthcare Informatics Research, 2010)
ObjectivesThe transmission of medical information is currently a daily routine. Medical information needs efficient, robust and secure encryption modes, but cryptography is primarily a computationally intensive process. Towards this direction, we design a selective encryption scheme for critical data transmission.MethodsWe expand the advandced encrytion stanard (AES)-Rijndael with five criteria: the first is the compression of plain data, the second is the variable size of the block, the third is the selectable round, the fourth is the optimization of software implementation and the fifth is the selective function of the whole routine. We have tested our selective encryption scheme by C++ and it was compiled with Code::Blocks using a MinGW GCC compiler.ResultsThe experimental results showed that our selective encryption scheme achieves a faster execution speed of encryption/decryption. In future work, we intend to use resource optimization to enhance the round operations, such as SubByte/InvSubByte, by exploiting similarities between encryption and decryption.ConclusionsAs encryption schemes become more widely used, the concept of hardware and software co-design is also a growing new area of interest.